Review: TASHI'S TURBINE - Alexander R, O'Neill (Asian Highlands Perspectives, 2018)
Amitabh Raj Joshi (director, producer). 2015. Tashi's Turbine. New York City, NY: Vacant Light LLC. 56 mins. http://bit.ly/2tg9fTx, Nepali and Lowa, English subtitles. Color. (Institutional use 320USD); (personal use 34.95USD). In the windswept valleys of Upper Mustang, Nepal, renewable energy is transforming lives. Micro-turbine projects have connected off-grid communities with basic electricity, providing hope for sustainable growth on the Roof of the World. The documentary Tashi's Turbine follows two friends as they experiment with these technologies in Nyamdok Village, along the Sino-Nepali border. Recognizing that high-mountain valleys, including Mustang, Palpa, and Khumbu, are rich in wind resources, Tashi and his friend, Jeevan Kumar Oli, attempt to mitigate poverty using grassroots energy. Tashi Bista was inspired in his youth by tales of "wind machines" at Kagbeni Village in Upper Mustang. In 1987, the Danish Government had funded a twenty-kilowatt turbine in the area; but, it was rapidly decommissioned due to maintenance complications. In 1996, the Government of Nepal established the Alternative Energy Promotion Center (AEPC) to revive this and other wind programs and address related challenges. Nevertheless, AEPC's latest Wind Energy Resource Assessment revealed two decades of inaction. Wind programs in other parts of the country remain nascent; much of Central and Western Nepal have yet to be connected to the national grid. Director and cinematographer Amitabh Raj Joshi cultivates a nuanced vision of these developments by juxtaposing majestic landscapes against simple homes and everyday struggles for existence. The film opens with panoramas of the sapphire skies and canvas valleys of Mustang. Minutes later, kerosene fixtures illuminate paltry yields from subsistence harvests; children attempt to study under candlelight, often to no avail. Voicing the narratives of villagers like Chhimi Lhamo, Karma Lutok, and Pemba Tashi, Joshi captures an ongoing, critical discourse within local communities about energy. Originally from Kathmandu, Amitabh has received several prestigious awards for exploring the intersection of sustainability and identity worldwide, including the Princess Grace JustFilms Grant (2012), The Shelley and Donald Rubin Foundation Grant (2013), and the Center for Asian-American Media Documentary Fund (2014). Tashi's Turbine is a valuable and light-hearted addition to the study of environment and society in South Asia. Most notably, it is a distinct pivot away from the dominant discourses of energy and hydropower which typically portray themes of relocation, damage, and loss. This film is not only inspirational, but also demonstrates the practical outcomes of grassroots action in Nepal. Outreach by people like Tashi and Jeevan can enhance the efficacy of NGOs by situating development projects within local contexts. Going forward, decentralized micro-grids may be a temporary solution to the energy demands in the Himalayas. My only criticism of the film is that its Nepali to English language translations are quite truncated. This does not necessarily disrupt the flow of dialogue, or the central message of the film. By December 2017, Nepal will complete the thirteenth iteration of its three-year development plan. It has endeavored to connect eighty-seven percent of households with electricity and make all homes smoke-free. Clearly, these lofty goals will not reach Nyamdok by that time, even with AEPC advocating sustainable energy. Tashi's Turbine remains a poignant reminder of communities who have not and will not receive the benefits of state programs for years to come.